Model Dakwah Bil Hal Sebagai Pendekatan Pemberdayaan Masyarakat (Kecamatan Baamang Kabupaten Kotawaringin Timur Kalimantan Tengah) - Norhasanah Putri; Asep Rahmatullah (Al-Wasathiyah: Journal of Islamic Studies, 2025)
Community empowerment through religious approaches requires strategies that integrate spiritual values with concrete actions to create sustainable social transformation. This study examines the implementation of dakwah bil hal model as a community empowerment approach in Baamang District, East Kotawaringin Regency, Central Kalimantan, focusing on analyzing supporting factors, obstacles, and model effectiveness in improving community welfare. The method employed is a qualitative approach with library research on scientific literature from 2021-2025 through qualitative content analysis. Findings indicate that dakwah bil hal successfully transforms the paradigm from verbal communication to concrete action through enabling, training, empowering, and protecting stages. Implementation success is supported by inclusive leadership, adaptation to local culture, and community trust in implementing institutions. Various programs such as waste bank management, water source expeditions, and tourism village empowerment have proven effective in improving economic welfare, strengthening social cohesion, and fostering community independence. The main constraint lies in limited human resource competencies in sustainable program management. This model provides strategic contributions to developing contextual, inclusive, and sustainable empowerment programs by holistically integrating economic, social, and spiritual dimensions.